PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI MINIMARKET SKY INDAH - Mungkur, Eliani; Purba, Daris (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2024)
This study aims to identify the effects of service quality, product variety, and location on purchasing decisions at Sky Indah Minimarket. A quantitative correlational approach was employed, with data collected through a questionnaire. The research population consisted of all consumers of Sky Indah Minimarket, including both repeat customers and first-time shoppers. The sample comprised 80 respondents selected using a sampling method. The analytical techniques included validity testing, reliability testing, descriptive analysis, classical assumption tests, and hypothesis testing. Multiple linear regression analysis was conducted using SPSS version 20. The results indicate that service quality and location have a significant effect on purchasing decisions, whereas product variety does not have a significant effect.